3D-Extrusion Manufacturing of a Kaolinite Dough Taken in Its Pristine State - Boyer, Séverine A. E.; Jandet, Lucie; Burr, Alain (Frontiers in Materials, 2021)
Ceramic is among the complicated materials to use in the design of fine objects. Complex shapes without any major defect are not easy to produce. In most of the cases, the production of ceramic parts is the results of three steps. Firstly, the "sculpture" of the raw piece by adding raw materials to lead to the final object. Secondly, the "drying" and finally the "high temperature oven-dry" of the dried raw object to transform the granular dough into a nice consistent compact material. Exploiting the special characteristics of ceramic is not only a thing of the past. Nowadays new possibilities, i.e. shapes and styles, can be offered in the use of ceramics, and especially where it concerns the application of the Additive Manufacturing (AM) concept. The combination of Computer Aided Design (CAD) to AM opens a completely new means of finding novel ways of processing final objects. By choosing to use kaolin clay without any chemical additions (or improvers) as ‘a model material’, the ability to produce controlled structures with freedom in design by additive deposition modeling is exposed. Discussions relate to the concomitant control of the process parameters, the kaolin hydration and the complexity of printed structures. The optimization of process parameters (nozzle speed, layer thickness, wall thickness) were defined with the calibration of the material flow. Both windows adjusting water content in dough (%wt) and imposing pressure in the tank of the 3D printer have been defined accordingly. The role of layer impression support was also found to be important. This study credits to use the state-of-the art technique (3D printing) to explore sustainable manufacturing of potteries.